FCM technique for efficient intrusion detection system for wireless networks in cloud environment. (October 2018) - Chen, Mingming; Wang, Ning; Zhou, Haibo; Chen, Yuzhi
Abstract: With the emergence of ad-hoc networks, the communication methods in the field of wireless have greatly developed. A great deal of research has been conducted, especially in mobile nodes or mobile ad hoc networks (MANETs). The greatest advantage of MANETs is that they don't require predefined infrastructures, such as router link, hub etc. The nodes in a MANET are capable of forming a network which is time-dependent but not permanent to establish communication based on the allocated path. Routing attacks can cause great damage to MANETs. In the past few years, the research work has proposed a special intrusion detection mechanism to detect these attacks, resulting in eliminating malicious nodes in the network. The proposed work in this research paper addresses an efficient fuzzy clustering based algorithm for intrusion detection of a MANET implementation in a cloud storage environment. This paper has presented a model and experimental justifications for improving the efficiency.